STUDI PEMANFAATAN CANGKANG KUPANG BERAS (Tellina sp) SEBAGAI BIOSORBEN UNTUK MENGOLAH AIR LIMBAH YANG MENGANDUNG ION LOGAM TEMBAGA (II) - Eko Santoso (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
Tellina sp (kupang beras) shells which are available in large quantities in Sidoarjo-East Java were ground to produce biosorbent powder for removal of Cu(II) ions from synthetic waste solutions. The removal process of Cu(II) ions was carried out by dynamic adsorption method using a fixed bed column. A quantity of the shell powder was put into the column and Cu (II) ion solution was delivered through bottom-up flow to the column using a pump at a certain flow rate in room temperature. An effluent, which came out from the column, was collected at a certain time interval. The Cu (II) ion concentration in the effluent was measured using Atomic Absorption Spectrophotometer (AAS). This research was carried out using varied depth of the shell powder of 2 cm (7.01 g), 2.5 cm (8.11 g), and 3 cm (9.90 g) and varied flow rate: of 0.5 mL/minute, 1.0 mL/minute, and 1.5 mL/minute. This research resulted in adsorption capacity of the shell powder increased with the increase of bed depth. At 1 mL/minute of flow rate the adsorption capacities were of 19.14, 21.89, and 22.82 mg/g for 2, 2.5, and 3 cm respectively of bed depth. The adsorption capacity also increased with the increase of flow rate, i.e., 14.36, 21.89, and 22.39 mg/g for 0.5, 1.0, and 1.5 of flow rate for 2.5 cm of bed depth respectively. Service time (tb) and volume treated (Vb) for 10 % of Cu (II) ions in the effluent increased also with bed depth by correlation coefficient of 0.9998. At bed depth of 2 cm, 2.5 cm, and 3 cm at flow rate of 1.0 mL/minute the service time was 10.86, 16.41, and 21.73 hours at 0.65, 0.98, and 1.30 L of volume treated. At the initial stage of research, pH of influent is 4 and the final value of effluent after treated process of the column is 7. After the treatment process, the shell powder loaded Cu (II) ions were regenerated using 0.01 N of EDTA disodium solutions at pH 9. For biosorbent column of 2.5 cm bed depth at flow rate of 1.0 mL/minute needed 160 hours of service time or 9.6 L of EDTA solutions for column regeneration.